(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper explores the use of allegory in Edmund Spenser’s The Faerie Queene through a political lens, analysing how the poem reflects and critiques the political, religious, and social climate of Elizabethan England. Written during the reign of Queen Elizabeth I, The Faerie Queene is a complex allegorical work that intertwines the narrative of knightly quests with broader themes of governance, virtue, and national identity. The paper argues that Spenser uses the allegorical structure to both celebrate and critique the political landscape of his time, particularly in relation to the Protestant Reformation, the monarchy, and England’s imperial aspirations. Central to this reading is the allegorical representation of Queen Elizabeth I as Gloriana, the Faerie Queene, whose reign is depicted as the ideal of divine and virtuous sovereignty. The poem’s various knights represent specific virtues essential to the stability of governance, such as justice, holiness, and temperance, reflecting Spenser’s ideal of leadership in England. The paper also examines how figures such as Duessa and the dragon symbolize foreign threats, especially Catholicism and its political and spiritual influence, and how these allegories mirror the ongoing conflict between Protestant England and Catholic Europe. Moreover, the paper addresses the political implications of gender in leadership, particularly through the character of Britomart, who challenges traditional notions of power by embodying female authority. Finally, the paper highlights Spenser’s critique of courtly intrigue, the dangers of bad counsel, and the portrayal of ideal kingship, suggesting that Spenser’s allegory offers both a vision of a virtuous monarchy and a cautionary tale about the vulnerabilities of political power. Ultimately, The Faerie Queene functions as a political and ideological commentary on Elizabethan England, offering insight into the complex relationship between virtue, governance, and national identity.